CHARLOTTE SMITH’S “BEACHY HEAD” AS A SPACE OF CONTRASTS - Şafak ALTUNSOY (Dokuz Eylül Üniversitesi Sosyal Bilimler Enstitüsü Dergisi, 2021)
ABSTRACT: This study concerns itself with the analysis of “Beachy Head” by Smith from the respect of prevalent contradicting forces such as Nature and culture or the historical time and the mythical past in the poem. The long narrative structure of the poem enables to present different voices reflecting the poet’s ideological stance towards the contemporary issues in her time and exemplifies the excluding attitude of the ones representing the Neoclassical values. The study, in this regard, tries to clarify the functionality of the contrasts in the poem and their influence on the possible meanings of the text. The tension and the Sublime in the poem appear in the way that the speaker observes Nature and her surroundings in order to grasp the circulations in the natural world and her private sphere. Accordingly, the concepts of time and place lead to alternative spatial and temporal experiences for the poetic persona. Then, the text also turns into a space in which the persona confronts not only the bloody history of humanity but also the consoling past experiences she has lost by integrating into the cultural world. The study concludes that “Beachy Head” goes beyond its geographical and natural qualities by offering both a corporeal journey and visionary progress for the poetic persona through certain dichotomies constructed and deconstructed throughout the text. ÖZ: Bu çalışma Smith’in “Beachy Head” (Kıyı Başı) adlı şiirini tarihsel zaman, mitik zaman, Doğa, kültür gibi baskın karşıt güçler ekseninde incelemektedir. Şiirin uzun ve anlatıma dayalı yapısı, şairin kendi zamanının sorunları konusundaki ideolojik tavrını göstermesine olanak sağlar ve neoklasik değerleri temsil edenlerin dışlayıcı tavrını da örnekler. Bu bakımdan çalışma, karşıtlıkların metin içindeki görevini ve metnin muhtemel anlamları üzerindeki etkisini açıklamaya çalışır. Şiirdeki gerilim ve Yüce kavramı hem doğal dünyadaki hem de içsel yaşamdaki döngüleri anlamak maksadıyla şiir kişisinin doğayı ve çevresini gözlemlemesi şeklindedir. Buna ek olarak, zaman ve mekân kavramları da şiir kişisi için alternatif zamansal ve mekânsal deneyimlere yol açar. Bu durumda metin, kişinin kültürel olana dahil olup kaybettiği iç rahatlatıcı geçmiş deneyimlerinin yanı sıra insanlığın kanlı tarihiyle de yüzleşeceği bir alana dönüşür. Çalışma, metinde kurulan ve bu kurulanın yapısının söküldüğü farklı karşıtlıklar vasıtasıyla “Beachy Head” adlı yerin hem bedensel hem de düşsel bir yolculuk olanağı sunarak doğal ve coğrafi niteliklerinin ötesine geçtiği sonucuna varır.